2015
DOI: 10.1002/ejoc.201403501
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Coupling of N‐Amino­azoles with 3‐Halo‐Substituted ­Quinolin‐2(1H)‐ones, Coumarins, Quin­oxalin‐2(1H)‐ones, and Chromenes

Abstract: An efficient and general palladium‐catalyzed coupling of 3‐bromoquinolin‐2(1H)‐ones, 3‐bromocoumarins, 3‐chloroquinoxalin‐2(1H)‐ones, and 3‐iodo‐2H‐chromenes with a variety of 1‐aminoazoles is described. The reaction proceeds cleanly in the presence of the Pd(OAc)2/4,5‐bis(diphenylphosphino)‐9,9‐dimethylxanthene (Xantphos) catalytic system to provide the coupling products in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…We found that the reaction of 3‐bromocoumarin 2 with 3‐bromosubstituted aniline 5 f (2 eq) in the presence of Pd(OAc) 2 /( o ‐Tol) 3 P as the catalyst and Et 3 N as a base in DMF was characterized by the yield to 57%. Increasing of the yield of compound 8 f (to 88%) was observed by using of Pd(OAc) 2 ‐Xantphos‐Cs 2 CO 3 , a versatile and efficient catalytic system for the coupling of a wide range of nitrogen‐containing nucleophiles, including amides, sulfonamides, and functionalized alkylamines with 3‐halogen substituted coumarins …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the reaction of 3‐bromocoumarin 2 with 3‐bromosubstituted aniline 5 f (2 eq) in the presence of Pd(OAc) 2 /( o ‐Tol) 3 P as the catalyst and Et 3 N as a base in DMF was characterized by the yield to 57%. Increasing of the yield of compound 8 f (to 88%) was observed by using of Pd(OAc) 2 ‐Xantphos‐Cs 2 CO 3 , a versatile and efficient catalytic system for the coupling of a wide range of nitrogen‐containing nucleophiles, including amides, sulfonamides, and functionalized alkylamines with 3‐halogen substituted coumarins …”
Section: Resultsmentioning
confidence: 99%
“…An alternate method was based on the condensation of salicylaldehydes with glycine derivatives . An efficient palladium‐catalyzed C−N bond coupling reaction between 3‐bromocoumarins and a variety of nitrogen containing nucleophiles (amides, sulfonamides, carbamates, amines, and ureas) or 1‐aminoazoles was described. Copper‐catalyzed in situ C ( sp 2 )‐NH 2 bond formation (coupling–reduction sequences) to provide 3‐aminocoumarins from 3‐bromocoumarins, has been achieved using sodium azide .…”
Section: Introductionmentioning
confidence: 99%